Primary Dysmenorrhea: Assessment and Treatment - Guimarães, Inês; Póvoa, Ana Margarida (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Primary dysmenorrhea is defined as menstrual pain in the absence of pelvic disease. It is characterized by overproduction of prostaglandins by the endometrium, causing uterine hypercontractility that results in uterine muscle ischemia, hypoxia, and, subsequently, pain. It is the most common gynecological illness in women in their reproductive years and one of the most frequent causes of pelvic pain; however, it is underdiagnosed, undertreated, and even undervalued by women themselves, who accept it as part of the menstrual cycle. It has major implications for quality of life, such as limitation of daily activities and psychological stress, being one of the main causes of school and work absenteeism. Its diagnosis is essentially clinical, based on the clinical history and normal physical examination. It is important to exclude secondary causes of dysmenorrhea. The treatment may have different approaches (pharmacological, non-pharmacological and surgical), but the first line of treatment is the use of nonsteroidal anti-inflammatory drugs (NSAIDs), and, in cases of women who want contraception, the use of hormonal contraceptives. Alternative treatments, such as topical heat, lifestyle modification, transcutaneous electrical nerve stimulation, dietary supplements, acupuncture, and acupressure, may be an option in cases of conventional treatments' contraindication. Surgical treatment is only indicated in rare cases of women with severe dysmenorrhea refractory to treatment.
Keywords: dysmenorrhea; menstrual cycle; pain; NSAIDs; hormonal contraception